Characterization and management of various renal cystic lesions by sonographic features. Issue 12 (December 2018) - Tay, Shee‐Yen; Tiu, Chui‐Mei; Hu, Bing; Wang, Hsin‐Kai; Chiou, Hong‐Jen; Lin, Yung‐Hui; Lai, Yi‐Chen; Chan, Wing P.; Chou, Yi‐Hong
Abstract : N/A: Renal cysts are common incidental findings in clinical practice. Most renal cysts detected in medical imaging are benign simple cysts. However, some are complicated by hemorrhage or infection or are associated with calcification. In these instances, difficulties can be encountered distinguishing the complicated cysts from cystic renal tumors such as cystic renal cell carcinoma, multilocular cystic nephroma, and mixed epithelial and stromal tumors. The Bosniak classification is widely used to categorize cystic renal lesions but is used to classify those discovered via computed tomography. Ultrasonography (US) and color Doppler US are the most frequently used imaging techniques for abdominal surveys and long‐term follow‐up because of their noninvasiveness, relatively low cost, wide availability, and frequently, lack of contrast medium. Herein, we review the features of various cystic lesions of the kidney that can be found using US, discuss differential diagnoses using US, and propose a feature‐oriented algorithmic approach to classifying renal cystic lesions using US.